Usefulness of myocardial work to predict long-term hard cardiovascular outcomes after ST-segment elevation acute myocardial infarction. (4th February 2022) - Timoteo, A; Moura Branco, L; Galrinho, A; Branco Mano, T; Rio, P; Viegas, J; Cruz Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background:  Left ventricular (LV) global longitudinal strain has demonstrated incremental prognostic value over LV ejection fraction (LVEF) in patients with ST-segment-elevation acute myocardial infarction. However, LV global longitudinal strain (GLS) does not take into consideration the effect of afterload. Myocardial work (MW) by speckle-tracking echocardiography integrates blood pressure measurements (afterload) with LV GLS and it has been recently demonstrated that Global Work Efficiency (GWE) predicts long-term all-cause mortality. It remains to be demonstrated if MW indices are associated with hard cardiovascular endpoints. The present study aimed to investigate the prognostic value of LV MW obtained from pressure-strain loops with echocardiography in patients with ST-segment-elevation myocardial infarction. Methods:  A total of 132 consecutive patients admitted with an ST-segment-elevation acute myocardial infarction (mean age 62 ± 12 years; 76% men) that survived to discharge were retrospectively analysed. LVEF, GLS and all LVMW indices were measured by transthoracic echocardiography before discharge (4.9 ± 2.4 days after admission). All patients had at least a two-year follow-up (mean follow-up of 820 ± 155 days). Outcomes: all-cause mortality, major acute cardiovascular events (a composite of cardiovascular mortality, myocardial infarction, stroke, unplanned cardiovascular admission) and heart failure hospitalization. Results:  In the two-year follow-up, 6 patients died, there were 18 patients with MACE, and 3 patients were hospitalized with heart failure. We confirmed that for all-cause mortality, GWE and GWI showed better discrimination compared to GLS (Table), with a cut-off of 83% and 1066 mmHg% (log-rank < 0, 001) respectively. However, ROC curve comparisons were not significantly different. For MACE, the performance of all methods is suboptimal, with an AUC < 0.65 for all variables, except for GLS. For heart failure admission, performance is slightly better, but GLS is still the best parameter to predict this event. Conclusions:  LVGWE and GWI are better predictors of all-cause mortality compared to GLS, but MW indices failed to demonstrate a prognostic impact in long-term cardiovascular events. Prospective studies are warranted to confirm this finding.